Miscellany of the South Seas A Chinese Scholar's Chronicle of Shipwreck and Travel through 1830s Vietnam - Tinglan, Cai (University of Washington Press, 2023)
In 1835 young Chinese scholar Cai Tinglan was caught in a typhoon while sailing across the Taiwan Strait. He and his shipmates spent a harrowing week at sea before drifting to the coast of central Vietnam. With an escort of Vietnamese soldiers, Cai traveled north along the famous "Mandarin Road," meeting governors-general of each province he passed through along his overland journey to Fujian Province in China. Cai documented his experiences in Miscellany of the South Seas (Hainan zazhu), a vivid account of clothing, food, religious practices, government affairs, and other aspects of daily life in early Nguyễn dynasty Vietnam. Cai's encounters with diasporic Chinese show the Hokkien merchant community's penetration into Vietnamese society, while his warm embrace by Nguyễn officials illustrates a shared elite world of classical culture across international borders. In this first English translation, Kathlene Baldanza and Zhao Lu provide a comprehensive introduction that puts Cai's account in social, political, and economic context, along with extensive annotation and a glossary.